2018
DOI: 10.12659/ajcr.911842
|View full text |Cite
|
Sign up to set email alerts
|

Hemangioma of a Male Breast: Case Report and Review of the Literature

Abstract: Patient: Male, 84Final Diagnosis: Breast hemangiomaSymptoms: Feeling breast massMedication: —Clinical Procedure: —Specialty: SurgeryObjective:Rare diseaseBackground:Male breast hemangioma is a rare benign neoplasm that is usually excised for definitive diagnosis.Case Report:In our case report, we present a male octogenarian with multiple comorbidities who presented with a large palpable mass in his right breast. The diagnostic imaging studies were suggestive of a benign tumor, with a BI-RADS (Breast Imaging Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Breast hemangiomas may occur at any age, even in childhood, with an age range between 18 months and 82 years [11]. Very rarely, hemangiomas may also present in association with breast implants [12] and in the male breast [13].…”
Section: Discussionmentioning
confidence: 99%
“…Breast hemangiomas may occur at any age, even in childhood, with an age range between 18 months and 82 years [11]. Very rarely, hemangiomas may also present in association with breast implants [12] and in the male breast [13].…”
Section: Discussionmentioning
confidence: 99%
“…Mammary hemangiomas were first described by Image and Hake in 1847 and the first operative case was by Sutton in 1889 [147]. They are defined as benign vascular lesions consisting of a mass of blood vessels [148]. There have been many types of hemangiomas described, with the first classification system described by Rosen in 2001 [149].…”
Section: Hemangiomamentioning
confidence: 99%
“…The differential diagnosis of a palpable mass in a male patient includes, but is not limited to, gynecomastia, pseudogynecomastia such as lipomastia, hemangioma, angiosarcoma, lymphangioma, fat necrosis, pseudoangiomatous stromal hyperplasia, and reactive lymphadenopathy. 7 …”
Section: Differential Diagnosismentioning
confidence: 99%
“… 9 A retrospective study by Mesurolle et al, and further highlighted by Yoga et al, concluded that it is reasonable to spare patients surgical excision of benign hemangiomas of the breast with a strong radiographic–pathologic correlation and a clearly benign diagnosis on biopsy. 7,10 The patient did not undergo surgery and close follow-up was recommended.…”
Section: Investigation/imaging/pathology Findingsmentioning
confidence: 99%
See 1 more Smart Citation